Open study

is now brainly

With Brainly you can:

  • Get homework help from millions of students and moderators
  • Learn how to solve problems with step-by-step explanations
  • Share your knowledge and earn points by helping other students
  • Learn anywhere, anytime with the Brainly app!

A community for students.

Problem Solving - Damped Harmonic Motion

I got my questions answered at in under 10 minutes. Go to now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Join Brainly to access

this expert answer


To see the expert answer you'll need to create a free account at Brainly

Is this a tutorial?
Damped SHM \[x = e ^{\frac{-r }{ 2m }t} (C _{1} e ^{i \omega t} + C_{2} e^{- \omega t}) \] a) when t = 0, then: \[x = A \cos \phi \] where: \[\frac{ dx }{ dt } = - \omega A \sin \phi \] approachable \[\frac{ r }{ m } \approx 0\] \[\phi = \frac{ \pi }{ 2 }\] calculate the value of C1 and C2! MY SOLUTION when t = 0 \[x(t) = e^{-\frac{ r }{ 2m }(t)} (C_{1} e^{i \omega (t)} + C_{2} e^{- i \omega (t)})\] \[x (0) = e ^{-\frac{ r }{ 2m } (0)} (C_{1} e^{i \omega (0)} + C_{2} e^{-i \omega (0)})\] \[x(0) = e^{0} (C_{1} e^{0} + C_{2}e^{0})\] \[x (0) = (C_{1}+ C_{2})\] because of when t=0, x = a cos phi \[x(0) = [C_{1}+ C{2}] = A \cos \phi\] \[[C_{1}+C_{2}] = A \cos \phi ........ (1)\] the next section \[\frac{ dx }{ dt } = \frac{ d }{ dt }(e^{-\frac{ r }{ 2m }t} [C_{1}e^{i \omega t} +C_{2}e^{-i \omega t}])\] \[\frac{ d }{ dt }(e^{i \omega t - \frac{ r }{ 2m }t} C_{1}) + \frac{ d }{ dt }(e^{-i \omega t - \frac{ r }{ 2m}t} C_{2})\] \[e^{i \omega t - \frac{ r }{ 2m }t} (i \omega - \frac{ r }{ 2m }) C_{1} + e^{-i \omega t - \frac{ r }{ 2m}t}(-i \omega -\frac{ r }{ 2m })\] when t = 0 \[\frac{ dx }{ dt } = e^{0} (i \omega - \frac{ r }{ 2m })C_{1} + e^{-0} (-i \omega - \frac{ r }{ 2m })\] because of : \[\frac{ dx }{ dt } = - \omega A \sin \phi \] Then \[e^{i \omega (0) - \frac{ r }{ 2m }(0)} (i \omega - \frac{ r }{ 2m }) C_{1} + e^{-i \omega (0) - \frac{ r }{ 2m}(0)}(-i \omega -\frac{ r }{ 2m })= - \omega A \sin \phi\] \[i \omega (C_{1} - C_{2}) - \frac{ r }{ 2m }(C_{1}+C{2}) = -\omega A \sin \phi\] when approachable \[\frac{ r }{ m } \approx 0\] then \[i \omega (C_{1} - C_{2}) -(0)(C_{1}+C{2})) = -\omega A \sin \phi\] \[i \omega (C_{1} -C_{2}) = - \omega A \sin \phi ......(2)\] when approachable \[\phi \approx \frac{ \pi }{ 2 } \] then based on a second (2) equation \[[C_{1}+C_{2}] = A \cos \phi\] \[[C_{1}+C_{2}] = A \cos 0\] \[[C_{1}+ C_{2}] \approx 0\] then \[C_{1}- C_{2} = -\frac{ A \sin \phi }{ i } = i A \sin \phi\] \[C_{1}+C_{2} = A \cos \phi ..... (3) \] \[C_{1}-C_{2} = i A \sin \phi ..... (4)\] for C1, add (3) and (4) \[(C_{1}+C_{2}) +(C_{1}-C_{2}) = A \cos \phi + i A \sin \phi \] \[(C_{1}+C_{1}) + (C_{2}-C_{2}) = A \cos \phi + i A \sin \phi\] \[2C_{1} = A \cos \phi + i A \sin \phi\] \[C_{1}= \frac{ A }{ 2 } (\cos \phi + i \sin \phi)\] \[C_{1} = \frac{ A }{ 2 } e ^{i \phi}\] for C2, subtract (3) and (4) \[(C_{1}+C_{2}) - (C_{1}- C_{2}) = A \cos \phi - i A \sin \phi\] \[C_{1}+C_{2} -C_{1} + C_{2} = A \cos \phi - i A \sin \phi\] \[2 C_{2} = A \cos \phi - i A \sin \phi\] \[C_{2} = \frac{ A }{ 2 } e^{-i \phi} \] Finally obtained the value of C1 and C2 \[C_{1} = \frac{ A }{ 2 } e ^{i \phi}\] \[C_{2} = \frac{ A }{ 2 } e^{-i \phi} \] The new equation of Damped Harmonic Oscillation \[x = e^{-\frac{ r }{ 2m }} [\frac{ A }{ 2 } e^{i \phi} e^{i \omega t} + \frac{ A }{ 2 } e^{-i \phi} e^{-i \omega t}]\] \[x = \frac{ A }{ 2 } e^{-\frac{ r }{ 2m }t} [e^{i (\omega t + \phi)} + e^{-i (\omega t + \phi)}]\]

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

I am not good at physics.....besides, I am not studying Physics this year... sorry I cannot help you...
@kryton1212 never mind pretty :D, it's my solution, it's my tutorial about Damped Harmonic Oscillation :D
@Shadowys Yes, of course, this is a tutorial :D
^ Proceeds to make things much more awkward than they would ever need to be.
@Schrodinger show me how you get it done :)
That look right to me! *
thank u @Fools101 :D
No problem ^_^ ! so how u been?
correct :)
thank u @Gabylovesyou :)
^ I'll do that as soon as I get through about three more semesters of college, at least, lol.
ok.., good luck @Schrodinger :)
  • hba
good going.
\([C1+C2]=Acos ϕ\) I don't understand why subbing \(ϕ≈\frac{π}{2}\) will result in \([C1+C2]=Acos 0\)
Other than that, it seems nice! :)
nice @Shadowys i mean \[[C_{1}+ C_{2}] = A \cos 90 = 0\] I'm sorry I made a mistake
@gerryliyana can u tell what partice r u talking about????????
i'm talking about solving the Damped Harmonic Motion Equation
So u r writing Transient solution of a general oscillator :) got it.............m i right????????
@gerryliyana ???????????
@Aperogalics i'm writing solution of special case at the damped condition of a oscillator
hei @tyzaQueen hbu?
@gerryliyana a tutorial
nice work
thank you @perl :)

Not the answer you are looking for?

Search for more explanations.

Ask your own question